First description of Escherichia coli producing CTX-M-15- extended spectrum beta lactamase (ESBL) in out-patients from south eastern Nigeria - Iroha Ifeanyichukwu R; Esimone Charles O; Neumann Sandra; Marlinghaus Lennart; Korte Miriam; Szabados Florian; Gatermann Sören; Kaase Martin (BMC, 2012)
Abstract We studied the presence of extended spectrum beta lactamases (ESBLs) in 44 clinical isolates of Escherichia coli collected from out-patients in two university teaching hospitals in South-Eastern Nigeria. Species identification was performed by standard microbiology methods and re-confirmed by MALDI-TOF technology. Phenotypic characterization of ESBL enzymes was done by double disc synergy test and presence of ESBL genes was determined by specific PCR followed by sequencing. Transfer of plasmid DNA was carried out by transformation using E. coli DH5 as recipient strain. Phenotypic characterization identified all isolates to be ESBL positive. 77% of strains were from urine, 13.6% from vaginal swabs and 9.0% from wound swabs. 63.6% were from female patients, 68% were from outpatients and 95.5% from patients younger than 30 years. All ESBL producers were positive in a PCR for blaCTX-M-1 cluster, in exemplary strains blaCTX-M-15 was found by sequencing. In all strains ISEcp1 was found upstream and ORF477 downstream of blaCTX-M. PCR for blaTEM and blaOXA-1 was positive in 93.1% of strains, whereas blaSHV was not detected, aac(6')-Ib-cr was found in 97.7% of strains. RAPD analysis revealed seven different clonal groups named A through G with the majority of the strains (65.9%) belonging to clone A. Transfer of an ESBL plasmid with co-resistance to gentamicin, kanamycin, tobramycin, doxycycline and trimethropim-sulfamethoxazole was successful in 19 (43.2%) strains. This study showed a high rate of CTX-M-1 cluster - ESBLs in South-Eastern Nigeria and further confirms the worldwide spread of CTX-M ESBL in clinical isolates.